Acute Pulmonary Thromboembolism – Use of Fibrinolysis to Treat a Hemodynamically Unstable Patient in the Era of the COVID-19 Pandemic: A Case Report - Jashari, Enes; Taravari, Hayber; Beqiri, Ardiana (Medical Publishing, d.o.o., 2021)
Pulmonary embolism (PE) is a common and potentially fatal condition. Despite advances in diagnostic procedures, late detection and non-detection of this condition is also not uncommon. In patients with PE, recurrent embolisms and death can be prevented with prompt diagnosis and adequate treatment. Due to presentation with a non-specific clinical picture and symptomatology, unfortunately almost one third of the patients remain undiagnosed and untreated. We know that there is a large difference in outcome between treated and untreated patients with PE (25-30% mortality in untreated and 2-8% in treated patients). We present a case of PE in the era of the COVID-19 pandemic in an adult patient with acute dyspnea, vomiting, presyncope, chest pain, and shock.
Keywords: pulmonary embolism; COVID-19; shock; fibrinolytic therapy